Methods in examining Sense-perception : John Philoponus and Ps.-Simplicius - Lautner, Peter (Laval théologique et philosophique)

(untitled) (Faculté de philosophie, Université Laval, 2008)
AbstractThe paper discusses the methods applied by Philoponus and Pseudo-Simplicius in commenting on Aristotle’s theory of sense-perception, and indicates their differences. Philoponus frequently employs medical theories and empirical material, mostly taken from Aristotle, to highlight not only the activities of the particular senses, but also a certain kind of awareness and the way we experience our inner states. By contrast, his Athenian contemporary Pseudo-Simplicius disregards such aspects altogether. His method is deductive : He relies on some general thesis, partly taken from Iamblichus, from which to derive theses on sense-perception. The emphasis falls on Philoponus’ doctrine since his reliance on medical views leads to an interesting blend of Platonic and medical/empirical theories.